Increased anxiety and synaptic plasticity in estrogen receptor β-deficient mice - Krȩżel, Wojciech (The National Academy of Sciences, 2001)
Estrogens are powerful modulators of neuronal physiology and in humans may affect a broad range of functions, including reproductive, emotional, and cognitive behaviors. We studied the contribution of estrogen receptors (ERs) in modulation of emotional processes and analyzed the effects of deleting ERα or ERβ in mice. Behavior consistent with increased anxiety was observed principally in ERβ mutant females and was associated with a reduced threshold for the induction of synaptic plasticity in the basolateral amygdala. Local increase of 5-hydroxytryptamine 1a receptor expression in medial amygdala may contribute to these changes. Our data show that, particularly in females, there is an important role for ERβ-mediated estrogen signaling in the processing of emotional behavior.